Conversion of Local Anesthesia–Guided Deep Brain Stimulation of the Subthalamic Nucleus to General Anesthesia - Kocabicak, Ersoy; Aygun, Dursun; Alptekin, Onur; Guz, Hatice; Kurt, Murat; Sarihasan, Binnur; Temel, Yasin (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2013)
Background Deep brain stimulation of the subthalamic nucleus (STN) is a widely applied procedure in the treatment of patients with advanced Parkinson disease and is generally performed under local anesthesia. Here we report our experience with the conversion to general anesthesia in two patients with advanced Parkinson disease because of fear reactions intraoperatively.Case Description Patients received general anesthesia with propofol and were implanted with electrodes at the level of STN guided by multiple-microelectrode electrophysiological recordings after obtaining informed consent. During the recordings the propofol levels were reduced. Postoperative clinical assessments showed marked improvements of motor disability with significant reductions of dopaminergic medication.Conclusion Our case observations document the possibility of fear reactions intraoperatively and show the possibility of conversion to general anesthesia with a successful outcome.
Keywords: subthalamic nucleus; general anesthesia; propofol; deep brain stimulation; Parkinson disease